'CRAMPED AND RESTRICTED AT HOME'? SCOTTISH SEPARATISM AT EMPIRE'S END*. (8th September 2015) - Nielsen, Jimmi Østergaard; Ward, Stuart
ABSTRACT: The emergence of Scottish separatism as a viable political force in the 1960s is often seen as a reflection of Britain's wider political fortunes in a post-imperial world. It is indeed the case that the Scottish National Party emerged from electoral obscurity to become a credible political alternative in the 1960s, culminating in Winifred Ewing's by-election victory in Hamilton in November 1967. That this occurred in the wake of Britain's retreat from empire fuelled speculation that separatist momentum in Scotland represented an inward manifestation of the same pressures that had torn the empire asunder. This paper draws on sources from local politics to make two key arguments: first, that post-imperial influences were neither as pervasive nor even particularly prominent in the local politics of devolution as may be assumed. Equally, however, global processes of decolonisation contributed to the separatist agenda in ways more subtle than has hitherto been acknowledged. Indeed, there are several striking similarities between the gathering political momentum of the SNP and the sweep of 'new nationalisms' through the remnants of the British world in the 1960s, particularly in the former British Dominions of Australia, Canada and New Zealand. Thus, the relative absence of decolonising discourse in the local electoral source material does not necessarily rule out these global undercurrents, although the exact nature of their influence needs to be more carefully evaluated.